Evaluation of the bactericidal capacity of vegetable extracts of Drimys granadensis with different polarities - Cuervo Salcedo, Daniela (2019)
Applying a cold maceration method and a fractioning with polar increasing solvents, four vegetable extracts of Drimys granadensis leaves were obtained: Very nonpolar (MA), nonpolar (A), polar (P) and very polar (MP); each one of them were obtained using hexane, chloroform, acetone and methanol correspondingly. Afterwards we followed the Minimum Inhibitory Concentration test (MIC) to determine the lowest concentration to inhibit the bacterial growth of two Gram positive strains: Staphylococcus aureus and Staphylococcus epidermis; and two Gram negative strains: Klebsiella pneumoniae and Escherichia coli. As a result, the polar fraction (P) was the most effective one by inhibiting the growth of all bacterial strains with a minimum concentration of 15 mg/mL.